Athletes as guest speakers in mathematics education: A descriptive study of a pala player in dialogue with pre-service teachers - Agirre-Basurko, Elena; Albizu-Mallea, Uzuri; Perales-Fernandez-de-Gamboa, Andrea (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
The integration of sports-related contexts into mathematics education, along with the inclusion of guest speakers in classroom settings, is a widely acknowledged pedagogical strategy. This study employs a descriptive research approach to analyze a didactic activity conducted with 86 third-year students pursuing a Degree in Primary Education at the University of the Basque Country. The chosen sport for this activity was Basque pala, featuring a guest speaker renowned as one of the sport's all-time greats. This activity aimed to enhance the future primary school teachers' capacity to develop and select appropriate mathematical educational materials. Data for this research comprise the mathematical inquiries generated by students' post-guest lectures and responses gathered from a post-session survey. Findings reveal that student participants held a notably favorable perception regarding using Basque pala as a mathematical context within primary school education and as a component of their pedagogical training. The involvement of the guest speaker received exceptionally high acclaim. These outcomes remained consistent across two academic years and regardless of respondents' gender. In summary, when introduced by a distinguished practitioner, Basque pala proved to be a fertile ground for generating mathematical tasks and was a highly motivating factor for pre-service teachers.